Implementation of Government Regulation in Granting Risk-Based Business Licensing at Private Job Training Institutions - Praya, Fajar; Utami, Tanti; Mulyana, Aji (Indonesian Journal Publisher, 2025)
This study examines the implementation of Government Regulation Number 5 of 2021 concerning Risk-Based Business Licensing for Private Vocational Training Institutions (LPKS) in Cianjur Regency, while also analyzing the strategic position of these institutions using a SWOT approach in responding to the Online Single Submission Risk-Based Approach (OSS RBA) system. The aim of this research is to assess the level of LPKS compliance with the OSS RBA system, identify the challenges they face, and evaluate the effectiveness of local government support. This study aims to analyze the level of compliance of Private Vocational Training Institutions (LPKS) in Cianjur Regency with the implementation of Government Regulation Number 5 of 2021 concerning Risk-Based Business Licensing (OSS RBA), as well as to identify various challenges that hinder its effective implementation at the local level.The findings reveal that out of 93 registered LPKS, only 9 have fulfilled the OSS RBA licensing requirements. The main obstacles include high costs associated with obtaining documents such as the Certificate of Proper Function (SLF), as well as a lack of understanding of the system. The SWOT analysis indicates that while LPKS have institutional potential and support, they still face significant internal and external challenges. Therefore, simplifying licensing procedures, enhancing technical assistance, and providing incentives for small-scale LPKS are crucial steps to improve compliance levels and the overall effectiveness of the OSS RBA system.